A Gigantic Shark from the Lower Cretaceous Duck Creek Formation of Texas - Frederickson, Joseph A.; Schaefer, Scott N.; Doucette-Frederickson, Janessa A. (My University, 2015)
Three large lamniform shark vertebrae are described from the Lower Cretaceous of Texas. We interpret these fossils as belonging to a single individual with a calculated total body length of 6.3 m. This large individual compares favorably to another shark specimen from the roughly contemporaneous Kiowa Shale of Kansas. Neither specimen was recovered with associated teeth, making confident identification of the species impossible. However, both formations share a similar shark fauna, with Leptostyrax macrorhiza being the largest of the common lamniform sharks. Regardless of its actual identification, this new specimen provides further evidence that large-bodied lamniform sharks had evolved prior to the Late Cretaceous.
Author Contributions Conceived and designed the experiments: JAF SNS JAD-F. Analyzed the data: JAF SNS. Wrote the paper: JAF SNS. Site data for OMNH V1727 are available by request from the department of vert. paleontology at the (SN)OMNH.
Keywords: vertebrae; sharks; ducks; teeth; Cretaceous period; limestone; shale; paleoecology